Environmental DNA reveals aquatic biodiversity of an urban backwater area, southeast coast of India. (October 2021) - Balasubramanian, Vignesh Kumar; Joseph Maran, Midhuna Immaculate; Ramteke, Darwin; Vijaykumar, Deepak Samuel; Kottarathail Rajendran, Abhilash; Ramachandran, Purvaja; Ramachandran, Ramesh
Abstract: Strong conservation management needs comprehensive data on biodiversity. Rapid methods that document aquatic biodiversity or assess the health condition of an ecosystem remain scarce. Herein, we have performed a metagenomics study on environmental DNA (eDNA) collected from an urban backwater area - Muttukadu, located in the southeast coast of India. Shotgun metagenomics approach using Illumina®NextSeq500 sequencing yielded 88.4 million raw reads. The processed data was assigned as 80% prokaryotes, 0.4% eukaryotes, ~2% viruses, and ~17% remain unknown. This approach has the potential to identify small micro-eukaryote, unseen species from both estuarine and marine environments. We have identified 156 eukaryote organisms represented from 21 phyla and 112 families, including those that are of conservational significance and ecological importance. Furthermore, our data also demonstrated the presence of pathogenic microorganisms due to sewage mixing with the backwaters. Given its sensitivity, we suggest this approach for an initial assessment of biodiversity structure in an ecosystem for the biomonitoring program. Highlights: First study that explores the biodiversity of Muttukadu backwaters through eDNA. eDNA-Illumina sequencing method facilitated to understand biodiversity of backwaters. A brief overview on the biodiversity constituents across major domains was studied. This includes invasive, alien and conservational valued species in backwater area. We recommend this approach for initial assessment on aquatic biomonitoring studies.